From eccentric to professional. The representation of women entrepreneurs in business magazines (Argentina, 1986-2010) - Garmendia, Magdalena (2025)
In recent decades, studies on entrepreneurship and gender as well as on business history have made important advances in understanding women in business. On the one hand, pioneering studies on entrepreneurship and gender have demonstrated the historical underrepresentation of women entrepreneurs and also, recently, their increasing incorporation under supposedly empowering narratives. On the other hand, in the field of business history, gender studies have provided meaningful insights into the incorporation of women into management and corporate boards. However, there are still no studies that investigate how women entrepreneurs have been represented in Latin America. In dialogue with both fields of study and with the intention to overcome this gap, this article analyzes the representation of women entrepreneurs in the business press in Argentina between 1986 and 2010. Based on the theoretical framework of cultural sociology and following a qualitative methodological strategy, this study focuses on Apertura, a widely circulated business magazine in this country. The article shows that, although the representation of entrepreneurs remains predominantly male, since the mid-1990s there has been a significant change in the narratives through which women have been represented (from atypical to professional). This paper concludes that this narrative shift has allowed for greater visibility of women entrepreneurs and thus legitimized female entrepreneurship.